Defensin gene polymorphism analysis in bovine intramammary infections of cattle and buffaloes of Gujarat - KUMARVERMA, AMIT; JOSHI, C G; KORINGA, P G; NAURIYAL, D S (The Indian Journal of Animal Sciences, 2011)
A study was carried out to identify polymorphism at defensin gene loci, responsible for expression of defensin secretion against infection of mammary gland. For this, blood samples were collected from Kankrej, triple cross, Holstein Friesian and buffaloes. From each category of cows and buffaloes, 6 samples were collected each from animals with clinical mastitis, subclinical mastitis and healthy udder. PCR-RFLP was carried out from the extracted genomic DNA. Four polymorphic patterns of combined defensin genotypes (CDG) were obtained. No significant correlation was observed between these groups of animals. Similarly, no breed correlation was recorded between animals with clinical and subclinical mastitis and healthy udder. It may be concluded that the indigenous Kankrej cattle and buffaloes located in Gujarat are genetically closer to each other than exotic and crossbred animals.